2010
DOI: 10.1159/000315552
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Value of Extratympanic Electrocochleography in the Diagnosis of Ménière’s Disease

Abstract: Objective: To evaluate the clinical conditions causing an elevation in the click-evoked summation potential (SP)/action potential (AP) amplitude ratio (SP/AP ratio), the cause of the SP enhancement in Ménière’s disease (MD) and the diagnostic efficacy of electrocochleography (ECoG) were discussed. Study Design: Retrospective case review. Setting: An outpatient clinic of the Otolaryngology Department of Kochi Medical School. Patients: ECoG testing was performed in 632 patients (727 ears) with vertigo/dizziness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
1
14
1
1
Order By: Relevance
“…The sensitivities and specificities of the Y width and RF values in the present study were at a similar or lower level relative to other tests for detecting endolymphatic hydrops, such as ECochG and VEMP. The sensitivity and specificity of ECochG in the diagnosis of MD have been reported to be 55-85 and 80-96%, respectively [Sass, 1998;Chung et al, 2004;Iseli and Gibson, 2010;Takeda and Kakigi, 2010]. Recently, Iseli and Gibson [2010] showed that by biasing the summation potential with low-frequency tone stimuli the sensitivity and specificity of ECochG were raised to 85 and 80.6%, respectively, separating MD patients from non-MD patients with an accuracy of 85% [Iseli and Gibson, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivities and specificities of the Y width and RF values in the present study were at a similar or lower level relative to other tests for detecting endolymphatic hydrops, such as ECochG and VEMP. The sensitivity and specificity of ECochG in the diagnosis of MD have been reported to be 55-85 and 80-96%, respectively [Sass, 1998;Chung et al, 2004;Iseli and Gibson, 2010;Takeda and Kakigi, 2010]. Recently, Iseli and Gibson [2010] showed that by biasing the summation potential with low-frequency tone stimuli the sensitivity and specificity of ECochG were raised to 85 and 80.6%, respectively, separating MD patients from non-MD patients with an accuracy of 85% [Iseli and Gibson, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Meniere's disease is a condition characterized by repeated vertiginous episodes accompanied by fluctuating hearing loss, tinnitus, and aural fullness [1][2][3]. However, symptom presentation can be vague and variable depending on the duration of the episodes.…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines have also provided a means to stage patients based on their audiometric status. Although the AAO-HNS's guidelines are applied to Meniere's disease based on clinical symptoms and audiometric data, most clinicians have felt the need for objective diagnostic tools [2][3][4][5]. To date, there is no objective, gold standard method for the diagnosis of Meniere's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we decided to use a simple non-invasive extratympanic form of ECoG. Takeda and Kakigi [12] reported that 56% of MD patients exhibited abnormal extratympanic ECoG findings, while that proportion was 44% in our study.…”
Section: Discussionmentioning
confidence: 71%